Post-lockdown clinics 2: 'You're gonna need a bigger boat'. Issue 7 (July 2020) - Howard, Nick; Tromans, Cindy
Abstract : As eye care practitioners return to a post-lockdown service, Nick Howard and Dr Cindy Tromans take a further look at ensuring both practitioner and patient safety as restrictions ease.